Reflectância espectral em avaliações sazonais do estado trófico das águas do reservatório Socepe em Itaara, Rio Grande do Sul - Facco, Douglas Stefanello (2018)
A lack of concern with maintaining water quality, sometimes in the intense degradation of the reservoirs which, as a consequence, reflect in the phenomena that occur in the hydrographic basin, whether of natural or anthropic origin. Excess nutrients are one of the main effects of land misuse in hydrographic basin of reservoir, considering that a higher load of nutrients implies an increase in phytoplankton productivity, that is, from primary productivity to levels that are considered natural, which influences the quality of water for many uses. From the determination of chlorophyll-a concentrations of phytoplanktonic organisms, water quality can be evaluated with the use of the Trophic State Index, that it is an indicator of the water based on the concentrations of one of the main nutrients phytoplankton: the total phosphorus. In addition to total phosphorus and chlorophyll-a, this index also considers the transparency of water. Of these variables, chlorophyll-a and water transparency are considered optically active, which allows their detection and determination from the use of remote sensing. In this context, the present work was inserted, with the objective of spatially and temporally the optically active variables indicative of the water quality of the reservoir SOCEPE, Itaara in the State of Rio Grande do Sul, and to develop an empirical model of estimation of these variables from Remote Sensing data. In order to achieve the objectives of the research, water samples and on-site measurements in loco were performed for the determination of optically active variables, water transparency, chlorophyll a and total suspended solids (TSS) in three field campaigns made in 01/04/2017, 08/31/2017 and 11/11/2017, which makes it possible to characterize the reservoir based on their seasonal variability. In addition, the TSI was calculated for water transparency and chlorophyll-a concentrations, being these variables together with the total suspended solids, also related to the water reflectance obtained by the Operational Land Imager (OLI) Sensor of the satellite Landsat-8, for the generation of empirical models for estimating them. In addition, the analysis of the influence of the hydrographic basin on the optically active variables, considering the of the vegetation verified from the Index of Vegetation by Normalized Difference (NDVI). Seasonal changes in relation to the optically active variables were verified. For chlorophyll-a, the highest concentrations were verified in the hottest seasons. The transparency of the water was lower in winter months, when the highest concentrations of total suspended solids were observed. The TSI varied seasonally and spatially from eutrophic to oligotrophic, with the main spatial variations occurring in the upper and lower reaches of the reservoir, evidencing the influence of the river basin on its waters, verified by the relationships between the greenery of the forest vegetation and the areas used for agriculture with optically active variables, highlighting the concentrations of suspended solids soil preparation periods for planting agricultural cultures. Considering the purpose of this study, it is possible to conclude that the techniques and methodologies used proved to be efficient for to adequately represent the seasonal dynamics and spatial variability of the variables analyzed and that the remote sensing data can allow the estimation of the optically active variables studied in the reservoir SOCEPE temporally and spatially.